Construction of ZnO/Cu2SnS3 nanorod array films for enhanced photoelectrochemical and photocatalytic activity. Issue 106 (1st November 2016) - Guo, Yuxiao; Yin, Xingtian; Yang, Yawei; Que, Wenxiu
Abstract : ZnO nanorod array films grown on fluorine-doped tin oxide glass substrates were homogeneously coated with visible light responsive Cu2 SnS3 nanoparticles through a controllable one-step electrodeposition process. Abstract : ZnO nanorod array films grown on fluorine-doped tin oxide glass substrates were homogeneously coated with visible light responsive Cu2 SnS3 nanoparticles through a controllable one-step electrodeposition process. The coating of Cu2 SnS3 nanoparticles expanded light utilization from the UV to visible region and facilitated charge generation, separation and transportation, thus leading to significantly enhanced photoelectrochemical and photocatalytic performance. The ZnO/Cu2 SnS3 nanorod array films with a deposition time of 90 s had the highest apparent rate constant (3.87 × 10 −2 min −1 ) and photocurrent density (0.46 mA cm −2 ), which were 2.86 and 23.00 times that of the pure ZnO, respectively. The ZnO/Cu2 SnS3 nanorod array films were proven to be an advanced structure for photoelectrochemical and recyclable photocatalytic applications due to the maintenance of the optimized Cu2 SnS3 nanoparticle coating and array nanostructure.